Analysis of the Portrayal of the Human Inner World in the Narratives of Shukur Kholmirzaev (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study explores the literary works of Shukur Kholmirzaev, a prominent writer who significantly influenced Uzbek literature during the 1960s. The focus is on examining how Kholmirzaev portrays the spiritual realm of individuals in his stories, a theme of relevance in fiction. Through a comparative analysis of various narratives by Kholmirzaev, insights into the writer's artistic representation of the human inner world are gained. The research particularly delves into Kholmirzaev's story "The Blue Sea," shedding light on his distinctive artistic style and receiving feedback from literary scholars and writers.